Ukraine war: will it lead to a new Bretton Woods? - Rana, Pradumna Bickram (2022)
Reforms of the 1944 US-led Bretton Woods global economic architecture have been implemented in a gradual and incremental manner. As the global context has changed considerably, can we expect more comprehensive reforms as called for by some? Will COVID-19 and the invasion of Ukraine have game-changing impacts on the global economic architecture?